Octane number influence on combustion and performance parameters in a Dual-Mode Dual-Fuel engine. (15th December 2019) - García, Antonio; Monsalve-Serrano, Javier; Villalta, David; Sari, Rafael
Highlights: Iso-octane and n-heptane blended to investigate five fuels with different octane number. Fuels with octane number from 92.5 to 87.5 provide optimum operation with diesel fuel. Fuels with octane number lower than 92.5 have low impact at low load conditions. Octane number effect evaluated on an equivalent driving cycle. Abstract: Low temperature combustion stands as a promising alternative to realize low soot and NOx emissions while achieving fuel consumption benefits compared to the conventional diesel combustion. Nonetheless, its applicability is limited to narrow zones inside the engine map, reducing the potential benefits on a real driving case. In this scenario, the use of dual-mode dual-fuel combustion stands as an alternative to cover engine conditions up to full load, avoiding the constraints of the fully premixed combustion whenever is needed. This combustion concept is strongly influenced by the characteristics of the fuels that are used to create the charge stratification during the engine operation. The current research aims to evaluate the influence of the low reactivity fuel octane number on the combustion process and the average performance and emissions results. Additionally, the best octane number was determined by means of a merit function evaluation. Octane values of 100, 92.5, 87.5, 85 and 80 were obtained by blending iso-octane and heptane. Their performance was assessed in a medium-duty multi-cylinder platform at different representative operating conditions. The results suggest that fuels with octane number lower than 92.5 have a low impact at low load conditions. However, as load is increased, the high reactivity of the low research octane number fuels leads to early combustion processes, demanding settings modifications to avoid the appearance of excessive pressure gradients. As a consequence of these modifications, the fuel consumption and soot emissions increase. In general, RONs from 92.5 to 87.5 are less penalized, presenting the best merit function values, and therefore being the best fuels to be used in the hardware under investigation.